STUDENTS’ PERCEPTION ON LANGUAGE PREFERENCE IN ENGLISH CLASSROOM (A STUDY CONDUCTED AT ENGLISH EDUCATION DEPARTMENT) - Vivianti Tamalawe; Nurmin Samola; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
This study is aimed at analysing purposeful language that students prefer in English classroom. It is to analyze the occurrence of code changes in language while communicating. The technique used in collecting data is questionnaires. The questionnaires are modified from Debreli and Oyman (2015). Data are analyzed using percentage formula by Riduwan (2014:28). Since the study is conducted at English Education Department, it is found that the material given by the lecturers are quickly understood if the language is used by the lecturers is mixed (English and Indonesian). The students of sixth semester (academic year 2020-2021) class A and B consist of 30 students who fill the questionnaires. The questionnaires consist of 10 questions with the intention of asking the students language preference in English classroom. For the number of those who respond to the question given is from number 1 to 10 that answer English 90 or 30 %, which answer English and Indonesian on the number 1 to 10 is 197 or 65,67 %, and which answers Indonesian on the question 1 to 10 is 12 or 4 %. Of the 10 questions that are shared with students and have been answered by students who prefer to use English and Indonesian in the process of learning to teach in the classroom between lecturers and students in order to be understood.